The effects of level and quality of education on a South African sample of English and African first language speakers, for WAIS-III digit symbol-incidental learning - Donnelly, Martin Joseph Rhodes (Rhodes University, Faculty of Humanities, Department of Psychology, 2001)
This study examined the effects of level and quality of education on WAIS-III Digit Symbol-Incidental Learning performance. The Pairing and Free Recall measures were administered to a South African sample (N = 68, age range 19-30), which was stratified for English and African language, level of education attained (Grade 12s and Graduates) and quality of education (advantaged and disadvantaged schooling). Results yielded no significant main or interaction effects between acculturation factors of level and quality of education. Normative guidelines of 13 or more pairs and 8 or more free recall symbols, appropriate to a non-clinical sample in a multicultural setting, are provided. Digit Symbol-Incidental Learning proved to be a culture-fair test, which contributes to its clinical utility as a sensitive memory screening tool.
Keywords: Wechsler Adult Intelligence Scale; Intelligence tests -- South Africa; Wechsler Adult Intelligence Scale -- South Africa